'It's Important for Us to Know How to Do Teamwork': Perceptions of Chinese International Hospitality Students Regarding Teamwork Skills. Issue 2 (3rd April 2021) - Sonnenschein, Katrine
ABSTRACT: This article investigates the perceptions held by Chinese international students at one Australian university regarding the importance of teamwork skills for entry-level positions in the Chinese hotel industry and the development of these skills. The findings from 19 semi-structured interviews demonstrate that most respondents feel that it is crucial for Chinese international students to develop teamwork skills for the Chinese hotel industry. Even though some respondents reported positive experiences working on university assignments with other students of different nationalities, others felt that cross-cultural teamwork was challenging due to their perceived weak English language skills and lack of creative ideas. Some students also mentioned that they would like their university lecturers and tutors to assist them in the formation and facilitation of teams. The article recommends structured interventions regarding cross-cultural teamwork and continuous English language teaching to familiarize the Chinese international students with the challenges that they may face.